Handbook on the law of cultural heritage and international trade - Nafziger, James A. R.; Paterson, Robert K., 1946- (Cheltenham, UK : Edward Elgar Publishing Limited, 2014)
This Handbook offers a collection of original writings by leading scholars and practitioners in the exciting, rapidly developing field of cultural heritage law. The detailed essays are the product of a multi-year project of the Committee on Cultural Heritage Law of the International Law Association. Following a comprehensive introduction to cultural heritage law, the book turns to the core topic of international trade. The General Agreement on Tariffs and Trade and a 1970 UNESCO convention on illegal trafficking in cultural material formed the foundation for progressive development of an impressive and still-evolving legal framework. Building on these and other instruments, the essays focus on import and export controls within specific national legal regimes. Concluding chapters contextualize additional important issues - including human rights, pluralism and nationalism - from a broader, global perspective. Innovative in its combination of comparative and international dimensions of the subject, this book provides a ready, well-documented reference to national and international regimes of control and a scholarly source for teaching and further research. Students, professors and practitioners of trade law, cultural heritage law and general international law will find this Handbook an invaluable resource.
This Handbook offers a collection of original writings by leading scholars and practitioners in the exciting, rapidly developing field of cultural heritage law.
Contents: Cultural Heritage Law James A.R. Nafziger and Robert Kirkwood Paterson 1. International Trade in Cultural Material James A.R. Nafziger and Robert Kirkwood Paterson 2. Australia Craig Forrest 3. Canada Robert Kirkwood Paterson 4. China James Ding 5. France Marie Cornu 6. Germany Kurt Siehr 7. Greece Elina N. Moustaira 8. Ireland Patricia Conlan 9. Israel Talia Einhorn 10. Italy Manlio Frigo 11. Japan Shigeru Kozai and Toshiyuki Kono 12. Mexico Ernesto Becerril 13. New Zealand Piers Davies and Paul Myburgh 14. Poland Andrzej Jakubowski and Olgierd Jakubowski 15. South Africa Margaret Beukes 16. Sweden Thomas Adlercreutz 17. Switzerland Marc-Andre Renold and Beat Schonenberger 18. Turkey Janet Blake 19. United Kingdom Kevin Chamberlain and Kristin Hausler 20. United States James A.R. Nafziger 21. Controls on the Export of Cultural Objects and Human Rights Kevin Chamberlain and Ana Vrdoljak 22. Foreign Objects and Nationalism Robert K. Paterson and Marc-Andre Renold 23. A Legal Pluralist Approach to International Trade in Cultural Objects Francesca Fiorentini
Includes bibliographical references and index.
Keywords: Cultural property -- Protection (International law); Foreign trade regulation